Biomolecular Mechanism Of Hyperbaric Oxygen Therapy As An Alternative Treatment In Autism Spectrum Disorder - Finnesia Arisca (Publication Department, Universitas Warmadewa, 2025)
Introduction Many alternatives have appeared in the recent technology days for Autism Spectrum Disorder (ASD), many which may have higher risks and harder compliance especially for children. Hyperbaric oxygen therapy (HBOT) has been in a lot of talks as an alternative treatment for ASD lately and showed improvements in the recent cases. This paper aims to elaborate about biomolecular mechanism involved and how it affect the symptoms of ASD. Methods This research was conducted using the electronic databases Pubmed, GoogleScholar, EBSCO, ScienceDirect, Ovid, Science, Springer, Scopus, Cochrane Database, Web of Science and Wiley Online Library for articles published between January 2020 and May 2025. Only peer-reviewed articles published in English were included. Results HBOT works by reducing tissue hypoxia, increasing mitochondrial function, restoring impaired blood circulation, anti-inflammatory effects, and many more. These effects help relieve psychological and behavioral symptoms of ASD, especially the alleviating effects on mitochondrial biochemical dysfunction. Conclusion Autism Spectrum Disorder (ASD) is a complex neurodevelopmental condition marked by difficulties in communication, social interaction, and repetitive behaviors. While its exact cause remains unclear, ASD cases in Indonesia are rising. Hyperbaric Oxygen Therapy (HBOT) shows potential in easing symptoms, particularly related to mitochondrial dysfunction, but its safety and efficacy need further study.